Determinants of the Unpaid Work in Slovakia - Alena Kascakova; Gabriela Nedelova; Mariana Povazanova (Statistika: Statistics and Economy Journal, 2013)
The article focuses on the exploring the unpaid work of people in the Slovak Republic. Eurostat methodology provides a precise list of certain activities in the household for which a person does not receive any remuneration. These activities are considered as unpaid work. The data are drawn from the results of the primary research conducted in the year 2012. The determinants of unpaid work are being studied separately for the groups of unpaid work activities and separately for the groups of people formed in compliance with their status activity. According to the model results the gender is a significant determinant of unpaid work. Among other determinants significant only for selected categories belong the following: age, educational level and status activity.